MEDIATING ROLE OF FINANCIAL PERFORMANCE IN THE EFFECT OF MACRO- AND MICRO-FUNDAMENTAL FACTORS ON THE FIRM VALUE - Muhammad Aliyudin; Yudi Nur Supriadi (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of macro and micro fundamental factors on the financial performance and value of non-financial SOEs in Indonesia using panel data for the 2017–2022 period. The results of the estimation show that micro fundamental factors have a significant role in improving financial performance and company value, while macro fundamental factors do not have a significant influence on these two variables. These findings confirm that internal company dynamics such as operational efficiency, capital structure, and profitability capacity are more decisive than external macroeconomic conditions. This study also found that financial performance does not have a significant effect on company value and does not mediate the relationship between macro and micro fundamentals on the value of SOEs. These conditions indicate that the capital market assesses SOEs through a broader perspective, including institutional reputation, governance, long-term stability, and government support. These results make an important contribution to the public financial management literature and confirm the differences in market behavior towards SOEs compared to private companies. In addition, the findings of the study provide strategic implications for SOE management to strengthen internal capabilities and improve the quality of information disclosure to be more in line with investor expectations and market dynamics.